Hubungan Kualitas Tidur, Obesitas dan Stres dengan Kejadian Hipertensi Pada Usia Lansia Awal (46-55 Tahun): Relationship between sleep quality, obesity and stress with hypertension in the early elderly (46-55 years) - Budiman Budiman; Nur Rizky Ramadhani; Syarifah Nur Ruliani (Open Access Jakarta Journal of Health Sciences, 2023)
Introduction: Hypertension can cause morbidity and mortality. Hypertension is also known as “silent murder” because people with hypertension often have no symptoms. Objective: This study aimed to determine the relationship between sleep quality, obesity and stress with the incidence of hypertension in the early elderly (46-55 years). Methods: This research is a quantitative type with an analytic nature. The research design used is a cross-sectional study. The population in this study is the early elderly age (46-55 years) in the Tidung Island Village Area in 2022 as many as 589 people. The sample in this study was 85 respondents. Determination of the sample in this study using a purposive sampling technique. The research instrument used was a questionnaire or questionnaire. Researchers used the Chi-Square test. Results: Based on the results of the study of sleep quality with hypertension incidence with P-value = 0.002, obesity with hypertension incidence with P-value = 0.005 and stress with hypertension incidence with P value = 0.033. Conclusion: There is a relationship between sleep quality, obesity and stress with the incidence of hypertension in the early elderly (46-55 years).